Three phase grid connected anti-islanding controller based on distributed generation interconnection - Abdolrasol, M.G.M.; Mekhilef, Saad (2010)
This paper proposes three phase grid connected anti-islanding controller based on distributed generation interconnection. This method is a combination of two detection methods namely active and passive. Firstly, Active islanding detection generates disturbances at the output of the distributed generation by use of Positive feedback and Continuous feedback signal injection which is based on DQ implementation. Secondly, passive islanding detection method is based on measuring the system parameters such as voltage, frequency, active and reactive power and total harmonic distortion (THD). This method use three phase RLC load and compares the performance of the technique with and without the anti islanding controller. Islanding conditions are simulated and verified with full analysis simulation and experimental result.